(untitled) (Research, Society and Development, 2020)
Nowadays companies are looking for ways to demonstrate their measures and visions regarding social and environmental responsibility, thus generating credibility to their brand. We can also notice a growing awareness among consumers, who have been opting for environmentally friendly products, and show great concern for the environment. Thus the present work proposes a greater visibility to this niche market, presenting some of the main natural assets most used in the production of organic cosmetics. It is also intended to present the characteristics of the “green consumer”. The green consumer is the one who values products free from animal cruelty, and who prioritizes products of entirely or partially plant origin, that do not degrade the environment, and have a sustainable beauty proposal. In this context, sustainability is defined as the set of attitudes that man takes in the use of natural resources and solutions for their particular and collective needs, responsibly, without aggression to the environment and ensuring the existence of these resources for future generations. To perform a literature review on the production of organic cosmetics, from its composition to its certification in the market. The methods employed in this work are based on bibliographic research. Twenty-five articles were selected in the databases, and seven were excluded because they were not addressing a subject consistent with the theme proposed in this study. Thus, 18 articles were used in the structuring of the present study. We can see that sustainable cosmetology is a theme increasingly addressed in our society, this market has gained prominence.